The Future of Gene Therapy for Transfusion-Dependent Beta-Thalassemia: The Power of the Lentiviral Vector for Genetically Modified Hematopoietic Stem Cells - Parin Rattananon; Usanarat Anurathapan; Kanit Bhukhai; Suradej Hongeng (Frontiers Media S.A., 2021)
β-thalassemia, a disease that results from defects in β-globin synthesis, leads to an imbalance of β- and α-globin chains and an excess of α chains. Defective erythroid maturation, ineffective erythropoiesis, and shortened red blood cell survival are commonly observed in most β-thalassemia patients. In severe cases, blood transfusion is considered as a mainstay therapy; however, regular blood transfusions result in chronic iron overload with life-threatening complications, e.g., endocrine dysfunction, cardiomyopathy, liver disease, and ultimately premature death. Therefore, transplantation of healthy hematopoietic stem cells (HSCs) is considered an alternative treatment. Patients with a compatible human leukocyte antigen (HLA) matched donor can be cured by allogeneic HSC transplantation. However, some recipients faced a high risk of morbidity/mortality due to graft versus host disease or graft failure, while a majority of patients do not have such HLA match-related donors. Currently, the infusion of autologous HSCs modified with a lentiviral vector expressing the β-globin gene into the erythroid progenitors of the patient is a promising approach to completely cure β-thalassemia. Here, we discuss a history of β-thalassemia treatments and limitations, in particular the development of β-globin lentiviral vectors, with emphasis on clinical applications and future perspectives in a new era of medicine.